Beyond structural determinism: advantages and challenges of qualitative social network analysis for studying social capital of migrants. (23rd September 2020) - Sommer, Elena; Gamper, Markus
Abstract: In this article we address the challenges and advantages of studying social capital of migrant entrepreneurs, applying a mixed‐method research design involving qualitative semi‐structured interviews and standardized network map data collection. Despite some limitations discussed in the article, the study illustrates that an applied methodological approach has a potential to overcome some of the pitfalls of 'structural determinism' by looking both at structural and contextual aspects as well as actors' active role in accessing and (re)shaping their business‐related networks across different geographic spaces. The article demonstrates that qualitative social network analysis is particularly valuable for emphasizing the role of human agency and temporal changes of social relations both in terms of network composition and network content as well as for exploring the meaning attached to social ties, potential access barriers to certain types of social capital and strategies to overcome these barriers.